TECHNOLOGY OF LASER CUTTING OF SILICON WAFERS INTO ORGANIC LIGHT-EMITTING DIODE CHIPS - V. S. Kondratenko; V. I. Ivanov (Российский технологический журнал)
The article deals with the matter of crystal quality in the production of microdisplays based on organic light-emitting diodes (OLEDs) after separation. This work aimed at increasing the product yield in cutting a silicon device wafer into chips by a method based on laser controlled thermocracking (LCT). This paper considers the laser processes performed on a laser system RT-350 assessed by the heating effect on OLED structures. Data for rating the merit of the surfaces of chips after the laser controlled thermocracking and dicing, namely, the availability and size of the chipping, as well as surface roughness are presented and compared. The authors substantiated the possibility of increasing efficiency and quality in the process of cutting silicon device wafers with a thickness of 725 microns into OLEDs for microdisplays production.